ISSUES OF VALUATION OF INVENTORIES IN ACCOUNTING - Khayitboyev Myxammadi Israpilovich (Research Parks Publishers, 2023)
This article describes the nature of inventories, their evaluation according to international standards and the procedure for disclosing them in financial statements.